Geometry of the Magma Chamber and Curie Point Depth Beneath Hawaii Island: Inferences From Magnetic and Gravity Data - Mohamed, Ahmed; Al Deep, Mohamed; Abdelrahman, Kamal; Abdelrady, Ahmed (Frontiers in Earth Science, 2022)
Land gravity and airborne magnetic data have been utilized to study the depth to the magmatic chamber using the Curie point depth and gravity inversion techniques beneath the active volcanoes of Hawaii Island. The accessibility to conduct some ground-based geophysical measurements in that area is difficult. The results indicate: (1) the depth to the deep magnetic sources are estimated at 8 km below the acquisition height, whereas the shallow magnetic sources are estimated at 1.3 km; (2) the estimated depth to the bottom of the magnetized rocks based on Curie depth point is varying from 0.93 to 12.4 km below the ground surface; (3) large plume of dense intrusive material is observed beneath the adjacent three volcanoes of Mauna Loa, Mauna Kea, and Kilauea at depth of ~1.0 km, and two small chambers are located beneath Kohala and Hualalai volcanoes with depths varying from 1.5 to 2.0 km; (4) gravity inversion technique indicates vertical rising magmatic plumes that are consistent with that estimated from the analysis of magnetic data; (5) the depth to the assumed magma layer is varying from 0.5 to 10 km based on the inversion of the gravity data; (6) the heat flow is showing high values close to the volcanic eruption zones; and (7) the Hawaii Island has high geothermal potential energy proximal to the volcanic eruption zones with shallower Curie point depths and higher geothermal gradient. The current study is informative and cost-effective for the most active volcanic area in the world.